The legal linguistic regime of cross-border service of documents in civil and commercial matters - Marino, Silvia (CUADERNOS DE DERECHO TRANSNACIONAL, 2026)
The present paper tackles the legal linguistic regime of service abroad according to the EU Regulations on the topic that succeeded over time, and the related case law. Far from being a purely technical procedural theme, it involves the rights of the parties to a fair trial. Therefore, the contribution addresses the issues of the object of the service and the language to be used; the ascertainment of the linguistic skills of the addressee; the identification of the interested parties in the service; the (un)lawfulness of the refusal. The last remarks cannot but be devoted to the digitalisation of the service, due to the recent entry into force of a new method of transmission, the electronic service.